Estimated epizoochory seed dispersal distances by grazing yak across seasons in an alpine meadow - Wang, Shulin; Hou, Fujiang (Frontiers in Plant Science, 2025)
IntroductionEpizoochorous dispersal of grassland plants by large herbivores is an important way by which grassland plants achieve population expansion over long distances. However, little is known about the maximum distance that seeds can be dispersed by domestic animals under seasonal grazing, which is the most common type of grassland management worldwide, especially in alpine regions.MethodsTo this end, we estimated the distance over which epizoochory dispersal occurs via yaks (Poephagus grunniens) for seven common plant species seeds in an alpine meadow under seasonal grazing using a simulated yak-fur seed adhesion test combined with observations of grazing behavior.ResultsThe results showed that, as yak primary (e.g., walking time) and secondary (e.g., foraging rate) behavioral patterns differed significantly across seasons (P< 0.05), the epizoochory dispersal distances of plant seeds also had clear seasonal dynamics, manifesting as spring > summer > autumn > winter, and that the length of seed adhesive structures correlated positively with the retention rate as well as retention time on yak fur. The relatively slow loss of diaspores observed in this study mainly shows that moving yak from one seasonal pasture to the following allows the dispersal of diaspores between two successive pastures. The dispersal scale was even wider (maximum dispersal distance of ~35 km) for seeds with special appendages (i.e., mucilage, sticking to the fur due to mucilage presence).DiscussionOur results highlight that yaks are substantial seed dispersal vectors for alpine meadow plants and that seasonal grazing is a suitable management method for coping with habitat fragmentation as well as plant diversity conservation in alpine areas from the perspective of seed dispersal.